Zero-dimensional tin-based perovskite material capable of efficiently emitting near-infrared light and preparation method and application of zero-dimensional tin-based perovskite material

By developing zero-dimensional tin-based perovskite materials, the problems of low photoluminescence quantum yield and poor thermal stability of near-infrared luminescent materials are solved, and high-performance green and environmentally friendly materials are realized, with the fields of electronic products and optoelectronic devices Huge potential.

CN119241474AActive Publication Date: 2025-01-03MINDU INNOVATION LAB +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411197516.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-03
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The existing near-infrared luminescent metal halide perovskite materials have problems with low photoluminescence quantum yield and poor thermal stability in terms of luminescence design, performance improvement and application, and due to the toxicity of lead, it is difficult to achieve practical commercial applications.

Method used

A zero-dimensional tin perovskite material has been developed with the chemical formula of (C8NH18)2SnX4, wherein X is selected from ClxBr1-x by mixing reactions of tin halide, bromide-N-propylmethylpyrrolidine and organic solvents , a monoclinic crystal zero-dimensional perovskite single crystal material with high luminous intensity and good crystallinity was prepared, and near-infrared light emission was achieved using ultraviolet light excitation.

Benefits of technology

It has achieved high-performance green and environmentally friendly, high-performance halide perovskite materials, solved the problems of toxicity and low luminous efficiency of lead-containing materials, and has huge development potential in the fields of electronic products and optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241474A_ABST
    Figure CN119241474A_ABST
Patent Text Reader

Abstract

The invention provides an efficient near-infrared light-emitting zero-dimensional tin-based perovskite material as well as a preparation method and application thereof. The chemical formula of the zero-dimensional tin-based perovskite material is (C8NH18) 2SnX4, X is selected from ClxBr1-x or Br, and x is selected from 0 to 1 and is not 0. The invention effectively solves the problems of toxicity of the known lead-containing perovskite material and low luminous efficiency of the near-infrared perovskite material, is expected to realize the application of the perovskite material in the fields of human electronic products and the like, and has huge development potential in the fields of luminous display, optoelectronic devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a zero-dimensional tin-based perovskite material with high-efficiency near-infrared luminescence, and a preparation method and application thereof. Background Art

[0002] Materials emitting in the near-infrared region are at the forefront of research and industry, mainly due to their wide applications in national security, non-destructive bio-imaging, long-wave communications, and photothermal conversion for healthcare. As an important member of the family of luminescent materials, metal halide perovskite materials have been demonstrated to emit light in the ultraviolet, visible, and near-infrared regions. Currently, near-infrared emitting metal halide perovskite materials have attracted great attention in various optoelectronic applications due to their low-temperature solution-processable synthesis, rich crystallographic / electronic structures, and unique optoelectronic properties. However, they still have some challenges in luminescent design, performance improvement, and application, such as low photoluminescence quantum yield and poor thermal stability, which hinder their practical application.

[0003] In recent years, lead-based halide perovskite materials have attracted extensive attention from researchers at home and abroad. However, the toxicity of lead has greatly hindered its practical commercial application. Therefore, it is imperative to explore metal halide perovskite materials with comparable optoelectronic properties to lead halide perovskites but lower toxicity. Among the many lead-free alternatives, tin, which is in the same family and has a similar shell electronic structure, is an ideal alternative element. Tin-based perovskites have semiconductor properties comparable to those of lead perovskites, including high absorption coefficient, high carrier mobility and ideal band gap. They are ideal materials for environmentally friendly perovskite solar cells and have been widely studied as non-lead halide perovskite materials. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A zero-dimensional tin-based perovskite material with the chemical formula (C8NH 18 )2SnX4, wherein X is selected from Cl x Br 1-x or Br, x is selected from 0-1 and is not 0.

[0006] According to an embodiment of the present invention, in the chemical formula, x is, for example, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9.

[0007] According to an embodiment of the present invention, the zero-dimensional tin-based perovskite material has good crystallinity and belongs to the monoclinic system.

[0008] According to an embodiment of the present invention, the zero-dimensional tin-based perovskite material has high luminescence intensity.

[0009] According to an embodiment of the present invention, the zero-dimensional tin-based perovskite material has a uniform morphology, and an average size of about 1-1000 μm, for example, 10 μm, 1000 μm.

[0010] According to an embodiment of the present invention, the zero-dimensional perovskite single crystal material exhibits single exponential decay, and the fluorescence lifetime is 1-10 μs, for example, 3 μs or 5 μs.

[0011] According to an embodiment of the present invention, the chemical formula of the zero-dimensional tin-based perovskite material is (C8NH 18 )2Sn(Cl x Br 1-x )4, x = 0.5, the average size is 10 μm; under 350nm ultraviolet light excitation, (C8NH 18 )2Sn(Cl x Br 1-x )4 Zero-dimensional perovskite single crystal material exhibits near-infrared light (830nm) emission.

[0012] According to an embodiment of the present invention, (C8NH 18 )2Sn(Cl x Br 1-x )4The fluorescence lifetime of zero-dimensional perovskite single crystal material is 4.6μs.

[0013] According to an embodiment of the present invention, the chemical formula of the zero-dimensional tin-based perovskite material is (C8NH 18 )2SnBr4, with an average size of 1000μm; under 360nm ultraviolet light excitation, (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material exhibits near-infrared light (840nm) emission.

[0014] According to an embodiment of the present invention, (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material has a fluorescence lifetime of 3.6μs.

[0015] The present invention also provides a method for preparing the above zero-dimensional tin-based perovskite material, the preparation method comprising the following steps:

[0016] 1) mixing tin halide, N-propylmethylpyrrolidine bromide and an organic solvent to obtain a mixed solution reaction liquid;

[0017] 2) Adding a reaction solvent into the reaction solution and allowing it to react to obtain the zero-dimensional perovskite single crystal material.

[0018] According to an embodiment of the present invention, the molar ratio of the tin halide to N-propylmethylpyrrolidine bromide is (0-4):(0-8) and the molar ratio is not 0, preferably (0.5-3):(2-5), exemplified by 1:2, 2:4.

[0019] According to an embodiment of the present invention, in step 1), the molar volume ratio of the tin halide to the organic solvent is 0.1-2 mol:1-10 mL, for example, 1 mol:5 mL.

[0020] According to an embodiment of the present invention, the organic solvent is selected from one, two or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone, N,N-dimethylacetamide, and N-methylpyrrolidone, preferably N,N-dimethylformamide.

[0021] According to an embodiment of the present invention, the reaction solvent is selected from one, two or more of acetone, chloroform, acetonitrile and toluene, preferably acetone.

[0022] According to an embodiment of the present invention, the volume ratio of the organic solvent to the reaction solvent is (1-10):(1-10), preferably (2-10):(2-10), and exemplarily is 5:5.

[0023] According to an embodiment of the present invention, in the step 1), the mixing is performed under an inert atmosphere and stirring conditions.

[0024] According to an embodiment of the present invention, the inert atmosphere is, for example, a nitrogen atmosphere.

[0025] According to the embodiment of the present invention, the stirring may adopt stirring conditions known in the art, and the present invention does not make any specific limitation, as long as the mixed solution can be obtained.

[0026] According to an embodiment of the present invention, in the step 1), the mixing is performed at a temperature of 50-150°C, preferably 50-100°C, exemplified by 50°C, 70°C, and 90°C.

[0027] According to an embodiment of the present invention, in the step 1), the mixing time is not specifically limited, as long as a mixed solution can be obtained.

[0028] According to an embodiment of the present invention, in the step 1), the mixing time is 0.5-1.5 hours, preferably 0.8-1.2 hours, and exemplarily 1 hour.

[0029] According to an embodiment of the present invention, in step 1), the mixed solution may also be filtered. Preferably, the filtration may be carried out by a method known in the art, which is not specifically limited in the present invention.

[0030] According to an embodiment of the present invention, in the step 2), the conditions for the static reaction include: a temperature of 20°C-40°C, exemplarily 25°C or 30°C; and a static reaction time of 1-48h, for example 24h.

[0031] According to an embodiment of the present invention, in the step 2), after the static reaction, the reaction liquid after the static reaction is further subjected to post-treatment, such as filtering; after filtering, the zero-dimensional perovskite single crystal material is obtained, which can be further washed.

[0032] The present invention also provides a zero-dimensional perovskite single crystal material prepared by the above preparation method, and the zero-dimensional perovskite single crystal material has the meaning as described above.

[0033] The present invention also provides applications of the zero-dimensional perovskite single crystal material in electronic products, such as applications in the fields of light-emitting displays, optoelectronic devices, etc.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention provides a green, environmentally friendly, high-performance halide perovskite material, which has a simple synthesis method, easy-to-control reaction conditions, and high repeatability.

[0036] 2. The present invention effectively solves the problems of toxicity of known lead-containing perovskite materials and low luminescence efficiency of near-infrared perovskite materials, and is expected to realize the application of perovskite materials in the fields of human electronic products, and has great development potential in the fields of luminescent display, optoelectronic devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the X-ray powder diffraction pattern of the zero-dimensional perovskite single crystal material in Examples 1 and 2;

[0038] Figure 2 It is a scanning electron microscope image of the zero-dimensional perovskite single crystal material in Examples 1 and 2;

[0039] Figure 3 It is the emission spectrum diagram of the zero-dimensional perovskite single crystal material in Examples 1 and 2;

[0040] Figure 4 This is the fluorescence lifetime diagram of the zero-dimensional perovskite single crystal material in Examples 1 and 2. DETAILED DESCRIPTION

[0041] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0042] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0043] Example 1

[0044] (C8NH 18 )2Sn(Cl x Br 1-x )4 The preparation of zero-dimensional perovskite single crystal material is as follows:

[0045] At room temperature, weigh tin chloride and N-propylmethylpyrrolidine bromide in a molar ratio of 1:2 and 5 mL of N,N-dimethylformamide in a glove box, add them to a 20 mL glass bottle, stir at room temperature for 30 min, then heat to 50 ° C and stir to dissolve for 1 h. Filter the clear and transparent reaction solution and place it in a new 20 mL glass bottle, then add 5 mL of acetone, let it stand at 30 ° C for 24 h, filter and wash to obtain near-infrared luminescent (C8NH 18 )2Sn(Cl x Br 1-x )4(x=0.5) zero-dimensional perovskite single crystal material.

[0046] See also Figure 1 As shown in (a), the near-infrared luminescent (C8NH 18 )2Sn(Cl x Br 1-x )4 The zero-dimensional perovskite single crystal material has good crystallinity, and its powder diffraction peak position and relative intensity are consistent with the single crystal X-ray diffraction data (see the standard line in the figure), belonging to the monoclinic crystal system.

[0047] See also Figure 2 As shown in (a), the near-infrared luminescent (C8NH 18 )2Sn(Cl x Br 1-x )4 The zero-dimensional perovskite single crystal material has high luminescence intensity, uniform morphology, and an average size of about 10μm.

[0048] See also Figure 3 As shown in (a), under 350nm ultraviolet light excitation, the (C8NH 18 )2Sn(Cl x Br 1-x )4 Zero-dimensional perovskite single crystal material exhibits near-infrared light (830nm) emission.

[0049] See also Figure 4 As shown in (a), under the excitation of OPO laser, the (C8NH 18)2Sn(Cl x Br 1-x )4 The zero-dimensional perovskite single crystal material presents a single exponential decay fluorescence lifetime diagram, and its fluorescence lifetime is 4.6μs.

[0050] Example 2

[0051] (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material is prepared as follows:

[0052] At room temperature, weigh tin bromide and N-propylmethylpyrrolidine bromide in a molar ratio of 1:2 and 5 mL of N,N-dimethylformamide in a glove box, add them to a 20 mL glass bottle, stir at room temperature for 30 min, then heat to 70 ° C and stir to dissolve for 1 h. Filter the clear and transparent reaction solution and place it in a new 20 mL glass bottle, then add 5 mL of acetone, let it stand at 30 ° C for 24 h, filter and wash to obtain near-infrared luminescent (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material.

[0053] See also Figure 1 As shown in (b), the near-infrared luminescent (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material has good crystallinity, and its diffraction peak position and relative intensity are consistent with the single crystal diffraction data (see the standard line in the figure), belonging to the monoclinic crystal system.

[0054] See also Figure 2 As shown in (b), the near-infrared luminescent (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material has high luminescence intensity, uniform morphology, and an average size of about 1000μm.

[0055] See also Figure 3 As shown in (b), under 360nm ultraviolet light excitation, the (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material exhibits near-infrared light (840nm) emission.

[0056] See also Figure 4 As shown in (b), under the excitation of OPO laser, the (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material presents a single exponential decay fluorescence lifetime diagram, and its fluorescence lifetime is 3.6μs.

[0057] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A zero-dimensional tin-based perovskite material, characterized in that: The chemical formula of the zero-dimensional tin-based perovskite material is (C8NH 18 )2SnX4, wherein X is selected from Cl x Br 1-x or Br, x is selected from 0-1 and is not 0.

2. The zero-dimensional tin-based perovskite material according to claim 1, characterized in that: The zero-dimensional tin-based perovskite material has good crystallinity and belongs to the monoclinic system. Preferably, the zero-dimensional tin-based perovskite material has high luminescence intensity. Preferably, the zero-dimensional tin-based perovskite material has a uniform morphology and an average size of about 1-1000 μm. Preferably, the zero-dimensional perovskite single crystal material exhibits single exponential decay, and a fluorescence lifetime of 1-10 μs.

3. The zero-dimensional tin-based perovskite material according to claim 1 or 2, characterized in that: The chemical formula of the zero-dimensional tin-based perovskite material is (C8NH 18 )2Sn(Cl x Br 1-x )4, x = 0.5, the average size is 10 μm; under 350nm ultraviolet light excitation, (C8NH 18 )2Sn(Cl x Br 1-x )4Zero-dimensional perovskite single crystal material exhibits near-infrared light emission. Preferably, (C8NH 18 )2Sn(Cl x Br 1-x )4The fluorescence lifetime of zero-dimensional perovskite single crystal material is 4.6μs.

4. The zero-dimensional tin-based perovskite material according to any one of claims 1 to 3, characterized in that: The chemical formula of the zero-dimensional tin-based perovskite material is (C8NH 18 )2SnBr4, with an average size of 1000μm; under 360nm ultraviolet light excitation, (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material exhibits near-infrared light emission. Preferably, (C8NH 18 )2SnBr4 zero-dimensional perovskite single crystal material has a fluorescence lifetime of 3.6μs.

5. The method for preparing the zero-dimensional tin-based perovskite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: 1) mixing tin halide, N-propylmethylpyrrolidine bromide and an organic solvent to obtain a mixed solution reaction liquid; 2) Adding a reaction solvent into the reaction solution and allowing it to react to obtain the zero-dimensional perovskite single crystal material.

6. The preparation method according to claim 5, characterized in that: In step 1), the molar ratio of the tin halide to N-propylmethylpyrrolidine bromide is (0-4):(0-8) and the molar ratio is not 0. Preferably, in step 1), the molar volume ratio of the tin halide to the organic solvent is 0.1-2 mol:1-10 mL.

7. The preparation method according to claim 5 or 6, characterized in that: The organic solvent is selected from one, two or more of dimethyl sulfoxide, N,N-dimethylformamide, γ-butyrolactone, N,N-dimethylacetamide and N-methylpyrrolidone. Preferably, the reaction solvent is selected from one, two or more of acetone, chloroform, acetonitrile and toluene.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The volume ratio of the organic solvent to the reaction solvent is (1-10):(1-10). Preferably, in step 1), the mixing is carried out under an inert atmosphere and stirring conditions. Preferably, in the step 1), the mixing is performed at a temperature of 50-150°C.

9. The preparation method according to any one of claims 5 to 8, characterized in that: In the step 1), the mixing time is 0.5-1.5 hours. Preferably, in step 2), the conditions for the static reaction include: a temperature of 20° C.-40° C.; and a static reaction time of 1-48 hours.

10. Application of the zero-dimensional perovskite single crystal material according to any one of claims 1 to 4 in electronic products.

Citation Information

Patent Citations

  • Organic-inorganic hybrid zero-dimensional non-lead perovskite material and synthesis method thereof

    CN111909696A

  • Zero-dimensional zinc-based blue-light perovskite nano material and preparation method and application thereof

    CN115612487A

  • Controllable preparation method of two-dimensional tin-based perovskite and application of two-dimensional tin-based perovskite in optical pumping

    CN116986992A

  • Electronic device including foldable conductive plate

    KR1020240031288A